Three-Dimensional Tissue Assemblies: Novel Models for the Study of Salmonella enterica Serovar Typhimurium Pathogenesis - Nickerson, Cheryl A. (American Society for Microbiology, 2001)
The lack of readily available experimental systems has limited knowledge pertaining to the development of Salmonella-induced gastroenteritis and diarrheal disease in humans. We used a novel low-shear stress cell culture system developed at the National Aeronautics and Space Administration in conjunction with cultivation of three-dimensional (3-D) aggregates of human intestinal tissue to study the infectivity of Salmonella enterica serovar Typhimurium for human intestinal epithelium. Immunohistochemical characterization and microscopic analysis of 3-D aggregates of the human intestinal epithelial cell line Int-407 revealed that the 3-D cells more accurately modeled human in vivo differentiated tissues than did conventional monolayer cultures of the same cells. Results from infectivity studies showed that Salmonella established infection of the 3-D cells in a much different manner than that observed for monolayers. Following the same time course of infection with Salmonella, 3-D Int-407 cells displayed minimal loss of structural integrity compared to that of Int-407 monolayers. Furthermore, Salmonella exhibited significantly lower abilities to adhere to, invade, and induce apoptosis of 3-D Int-407 cells than it did for infected Int-407 monolayers. Analysis of cytokine expression profiles of 3-D Int-407 cells and monolayers following infection with Salmonella revealed significant differences in expression of interleukin 1α (IL-1α), IL-1β, IL-6, IL-1Ra, and tumor necrosis factor alpha mRNAs between the two cultures. In addition, uninfected 3-D Int-407 cells constitutively expressed higher levels of transforming growth factor β1 mRNA and prostaglandin E(2) than did uninfected Int-407 monolayers. By more accurately modeling many aspects of human in vivo tissues, the 3-D intestinal cell model generated in this study offers a novel approach for studying microbial infectivity from the perspective of the host-pathogen interaction.